Cost-effectiveness of therapeutic approaches to acute lymphocytic leukemia in pediatric patients (Research, Society and Development, 2021)
Objective: To carry out a cost-effectiveness analysis of the most used antineoplastic treatment protocols of acute leukemia in pediatric patients. Methods: Conducted a cost-effectiveness analysis, using the decision tree model, based on the consultation of secondary data from health information systems in Brazil, SIGTAP - SUS. The population consisted of pediatric patients registered in RHC database of INCA, aged 0 to 19 years, showing lymphocytic / lymphoid / lymphoblastic leukemia as a neoplasm basis, in a period from 1997 to 2017. Results: For male patients, bone marrow transplantation (BMT) exhibited a high increase in the ratio as alternatives and demonstrated the least effectiveness. Despite high incremental costs, the treatment performed with Ct associated with BMT (CtMT), showed effectivess much higher than other alternatives, becoming a cost-effective treatment. The association of Ct with radiotherapy (CtRxt) revealed the most effective treatment. For females patients, the treatment performed with CtBMT has shown to be the least cost-effectiveness, along with BMT. In turn, CtRxt provides to be the best cost-effectiveness treatment. Conclusion: The results of this economic analysis revealed better cost-effectiveness for CtRxt and worse cost-effectiveness for BMT, in both sexes. This analysis showed different scenarios according to the patient's gender, in particular, treatment with CtBMT can be an effective therapeutic option for male patients, but not for female patients.